2010
DOI: 10.1080/17451000903150363
|View full text |Cite
|
Sign up to set email alerts
|

The near-bottom plankton community at the Porcupine Abyssal Plain, NE-Atlantic: Structure and vertical distribution

Abstract: The study presents results on the composition and vertical distribution of the near-bottom plankton community at an abyssal site in the NE Atlantic. Plankton samples were collected at 1, 15, 50 and 100 m above bottom (mab). Whereas the composition within the upper three layers was very similar, a major shift occurred in the immediate vicinity of the seafloor. Between 100 and 15 mab, the plankton was dominated by Copepoda, making up more than 75% of the total abundance and biomass (without gelatinous organisms)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…However, at these sites the authors suggested low biomass values may have made differences in biomass more difficult to detect. Strong taxonomic shifts with decreasing height above the seafloor have also been documented (Childress et al, 1989;Angel, 1990;Mees and Jones, 1997;Dauvin and Vallet, 2006), even in areas with low values and weak biomass depth gradients (Christiansen et al, 1999(Christiansen et al, , 2010. In the present study, although bioluminescent events could only be classified into broad faunal groups, different altitude patterns were discerned.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…However, at these sites the authors suggested low biomass values may have made differences in biomass more difficult to detect. Strong taxonomic shifts with decreasing height above the seafloor have also been documented (Childress et al, 1989;Angel, 1990;Mees and Jones, 1997;Dauvin and Vallet, 2006), even in areas with low values and weak biomass depth gradients (Christiansen et al, 1999(Christiansen et al, , 2010. In the present study, although bioluminescent events could only be classified into broad faunal groups, different altitude patterns were discerned.…”
Section: Discussionsupporting
confidence: 43%
“…Other studies with good sample sizes confidently report faunal increases towards the seafloor (Hargreaves et al, 1984;Roe et al, 1990;Robison et al, 2010), while others report increases only in specific faunal groups (Domanski, 1986;Childress et al, 1989;Vinogradov, 2005). There are also reports of no significant increase in biomass or abundance (Roe et al, 1990;Christiansen et al, 1999Christiansen et al, , 2010, although weak trends may be noted. The non-universality of increased near seafloor biomass and abundance is not surprising.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The organisms that inhabit the BBL can spend all or multiple periods of their lives in this zone. The hyperbenthic community composition differs significantly from that of the water column above it (Christiansen et al, 2010). These animals represent potential prey for benthic, pelagic, and demersal species, coupling pelagic and benthic food webs.…”
Section: Benthic Biologymentioning
confidence: 99%